Exploring the potential of the European Portfolio for Student Teachers of Languages (EPOSTL) as a reflective tool in initial primary teacher education. Issue 3 (3rd July 2019) - Ní Dhiorbháin, Aisling
Abstract : Although primary teachers in the Republic of Ireland are generalist teachers, language teaching of both Irish and English, as well as the development of literacy skills across the curriculum is an integral part of their daily professional practice. This paper presents an analysis of the European Portfolio for Student Teachers of Languages (EPOSTL) with a view to considering its potential as a reflective tool in the initial primary teacher education (IPTE) in the Republic of Ireland. The creation and structure of the EPOSTL within a European language policy landscape is delineated, and thematic analysis is presented, focusing on three of the EPOSTL's main theoretical and conceptual underpinnings: (a) teacher autonomy, (b) reflective practice and, (c) self-assessment. The role of primary teachers as language teachers within a new framework of plurilingualism is highlighted. In order to consider the suitability of the EPOSTL as a reflective tool in teacher education, IPTE educational policy documents are examined to uncover converging discourses with the underlying themes of the EPOSTL. The EPOSTL emerges as a good conceptual fit with IPTE policy. It presents as a reflective tool with the potential to promote a transformative and integrated approach to language teacher education in and across Institutes of Education at a time of sociolinguistic and curriculum change in Irish primary schools.